The Relationship of Serum Vitamin D Level With the Outcome in Surgical Intensive Care Unit Patients - Sanaie, Sarvin (Iran J Pharm Res, 2019)
The aim of this study was to assess the correlation of serum vitamin D with ICU length of stay, mortality rate, length of mechanical ventilation, and incidence of sepsis. We conducted a descriptive analytic study on 793 patients admitted to surgical ICU wards in northwest of Iran from March 2015 to March 2016. Patients were assessed during the ICU stay and the following data were collected: Glasgow Coma Score (GCS), APACHE II score, incidence of sepsis, duration of mechanical ventilation, LoS, mortality rate, and laboratory data (such as serum vitamin D, calcium, phosphorus, etc). The effect of vitamin D deficiency and the confounding factors on length of stay was assessed using the multinomial regression. Of 793 patients, 161 patients (20.3%) were in vitamin D deficiency group, 306 (38.6%) in vitamin D insufficiency group, 326 (41.1%) in vitamin D sufficiency group. Vitamin D deficiency increased risk of sepsis (OR = 22.93; 95%CI: 10.631-49.78) and mortality rate (OR = 42.93; 95%CI: 15.2-121.22). Vitamin D deficiency/insufficiency is a result of chronic and severe comorbidities of patients and can be considered as a helper but not a real risk factor for mortality and its level should be assessed in surgical critically ill patients. The way that various levels of vitamin D impact outcome in critically ill patients remains to be elucidated and further multi-center trials are needed to validate our results.